GIGANTEA orthologs, E2 members, redundantly determine photoperiodic flowering and yield in soybean. Issue 1 (5th January 2023) - Wang, Lingshuang; Li, Haiyang; He, Milan; Dong, Lidong; Huang, Zerong; Chen, Liyu; Nan, Haiyang; Kong, Fanjiang; Liu, Baohui; Zhao, Xiaohui
ABSTRACT: Soybean ( Glycine max L.) is a typical photoperiod‐sensitive crop, such that photoperiod determines its flowering time, maturity, grain yield, and phenological adaptability. During evolution, the soybean genome has undergone two duplication events, resulting in about 75% of all genes being represented by multiple copies, which is associated with rampant gene redundancy. Among duplicated genes, the important soybean maturity gene E2 has two homologs, E2‐Like a ( E2La ) and E2‐Like b ( E2Lb ), which encode orthologs of Arabidopsis GIGANTEA (GI). Although E2 was cloned a decade ago, we still know very little about its contribution to flowering time and even less about the function of its homologs. Here, we generated single and double mutants in E2, E2La, and E2Lb by genome editing and determined that E2 plays major roles in the regulation of flowering time and yield, with the two E2 homologs depending on E2 function. At high latitude regions, e2 single mutants showed earlier flowering and high grain yield. Remarkably, in terms of genetic relationship, genes from the legume‐specific transcription factor family E1 were epistatic to E2 . We established that E2 and E2‐like proteins form homodimers or heterodimers to regulate the transcription of E1 family genes, with the homodimer exerting a greater function than the heterodimers. In addition, we established that the H3 haplotype of E2 is the ancestral allele and is mainly restricted to low latitude regions, from which the loss‐of‐function alleles of the H1 and H2 haplotypes were derived. Furthermore, we demonstrated that the function of the H3 allele is stronger than that of the H1 haplotype in the regulation of flowering time, which has not been shown before. Our findings provide excellent allelic combinations for classical breeding and targeted gene disruption or editing. Abstract : A working model explains the asymmetric redundancy of E2 family members in flowering and adaptation in soybean according to their geographical distribution and molecular experiments. The diversified allele combinations of E2 family members allow the adaptation to different eco‐regions, which should contribute to soybean improvement.